Maximizing return on investment without increasing project risks — Near-shoring as a key practice on a business transformation programme: Case study on a training project for a global consumer goods company - Pereira, L.; Guedes, J. F. (2015 10th Iberian Conference on Information Systems and Technologies (CISTI), 2015)
Proximity off-shoring (near-shoring) on the Information Technology sector has been a common practice over the past 2 decades, mainly for software development functions. But the benefits harvested from the delivery of professional services on a near-shore model can be replicated to other functions from a business transformation programme, such as competence and training management projects, improving cultural affinity at an overall effective cost, reducing complexity and risks associated with remoteness. Using a large business transformation programme from a global consumer goods company as a single case study, the present paper analyses the benefits and main challenges of incorporating such delivery model in these types of projects, focusing its attention mainly on the financial and quality aspects. The analysis suggests that, when compared to traditional services delivery (on-site consultants), near-shoring practices can have a very positive financial impact for the vendor and the customer, translating into an increase on the Return on Investment (ROI) without a significant increase of risks or losses in quality – The service’s cost can have a significant reduction on the vendor side, with a consequent reduction to the end client. Regardless these benefits, it is suggested that traditional consulting still plays an unreplaceable role in these types of projects, especially by providing expert insights on the industry/solution and specifics of the local market and culture. Furthermore, it is suggested that it is equally important the commitment from top management for such initiatives, with the implementation of a clear and focused governance model to reduce eventual risks from remoteness or cultural clashes. Finally, the article also points out some directions for further research on the topic.